Lecture notes : ophthalmology - James, Bruce; Bron, Anthony J. (Oxford Wiley-Blackwell, 2011)
The book provides an introduction to ocular anatomy and eye examination and then focuses on core conditions in ophthalmology. Contents include: uveitis; glaucoma; retinal vascular disease; disorders of the visual pathway; eye movements and their disorders; tropical ophthalmology - eye diseases in the developing world; services for the visually handicapped.